Cancellations of elective surgical procedures due to inadequate management of chronic medications. (21st February 2019) - de Lorenzo‐Pinto, Ana; Ortega‐Navarro, Cristina; Ribed, Almudena; Giménez‐Manzorro, Álvaro; Ibáñez‐García, Sara; de Miguel‐Guijarro, Ángeles; Ginel‐Feito, María Dolores; Herranz, Ana; Sanjurjo‐Sáez, María
Summary: What is known and objectives: Inadequate management of chronic medication puts patients at risk and causes unnecessary suspension of surgical procedures. The objective of the study was to calculate the rate of cancellation of elective surgical procedures due to inadequate management of chronic medications and to analyse the underlying causes of cancellation. Methods: We designed an analytic, observational, retrospective study of all elective surgical procedures performed from July to October 2017 in a tertiary hospital. The main variable was the percentage of surgeries cancelled owing to inadequate management of chronic medications. Other variables recorded included demographic characteristics, time between the preanaesthesia evaluation and surgery, drug involved, and the reason for incorrect management of the medication. Results: During the study period, 5415 surgical procedures were programmed, and 793 (14.6%) were cancelled. Cancellations due to inadequate patient preparation accounted for 5.3% (42 cases), and 19 were related to incorrect medication management (2.4% of the total number of cancellations). The 19 patients, who were mostly men (73.7%), had a median age of 76 years (IQR 68‐81). The drugs involved were acenocoumarol (6), enoxaparin (4), clopidogrel (4), direct‐acting oral anticoagulants (2), acetylsalicylic acid (1), tocilizumab (1) and leflunomide (1). The reasons for drug mishandling were poor understanding of the anaesthesiology recommendations (15) and lack of a preanaesthesia evaluation (4). What is new and conclusion: Inadequate management of chronic medications (2.4%) is not the most frequent reason for cancellation, although it is one of the easiest to avoid. Based on our results, starting in October 2017, the Pharmacy Department began to offer a pharmaceutical service to patients with doubts about the preoperative management of chronic medications. Abstract : 793 elective surgeries were canceled between July and October 2017. 2.4% of them were related to incorrect medication management. Drugs involved were mostly anticoagulants and antiplatelet drugs.